Implementing Strengths-Based Approaches for Furthering Career Construction: Validation of the Academic Version of the Values in Action Character Strengths Scale for Assessing University Students’ Adaptability - Green, Zane Asher; Karuppannan, Gunasegaran (2025)
This research demonstrated the validation and application of the Character Strengths Scale for University Students (CSSUS)—a new measure for assessing adaptability. The research was based on three studies (n = 372; n = 368; n = 378) of Pakistani undergraduate students. In Study 1, EFA indicated a four-factor structure of the CSSUS. In Study 2, because of the strong correlations between the factors, the first-order CFA model was compared with a unidimensional model, second-order model, and bi-factor model. Results indicated that as compared to the three competing models, the first-order CFA model had the best fit. The four factors demonstrated appropriate convergent validity and tests of divergent validity indicated that each was distinct from the other. The factors showed adequate concurrent validity as each was related to proactive personality, core self-evaluations, and well-being. The factors also showed adequate internal consistency reliability. In Study 3, the academic virtues added unique variance to career adaptability above and beyond gender, age, personality traits, and domain-general character virtues, suggesting incremental validity of the scale. Finally, a strengths-based application of the CSSUS indicated that optimism may offer a pathway forward to enable university students to apply the four academic virtues to augment career adaptability.